2020
DOI: 10.1097/pcc.0000000000002505
|View full text |Cite|
|
Sign up to set email alerts
|

Nurse-Implemented Goal-Directed Strategy to Improve Pain and Sedation Management in a Pediatric Cardiac ICU

Abstract: Objectives: To assess the impact of a nurse-implemented goal-directed sedation strategy on patient care and nursing practice in a pediatric cardiac ICU. Design: Quality improvement project with a pre-post interval measurement plan. Setting: Thirty-one bed pediatric cardiac ICU in a freestanding tertiary care children’s hospital. Patients: Postoperative pediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…A previous large cluster RCT conducted in 31 PICUs could not show a significant reduction of ventilator time after the implementation of nurse goal-directed sedation protocol, but intubated patients spent significantly more days awake and calm while being intubated [ 40 ]. Other studies could show a reduction of opioids and benzodiazepines [ 41 , 42 ], as well as a reduction in PICU length of stay with implementation of nurse-driven protocolized sedation [ 43 ]. Whether the use of nurse-driven sedation protocols should be implemented or not, could be debated, but the abovementioned evidence show more advantages than drawbacks with such an approach.…”
Section: Discussionmentioning
confidence: 99%
“…A previous large cluster RCT conducted in 31 PICUs could not show a significant reduction of ventilator time after the implementation of nurse goal-directed sedation protocol, but intubated patients spent significantly more days awake and calm while being intubated [ 40 ]. Other studies could show a reduction of opioids and benzodiazepines [ 41 , 42 ], as well as a reduction in PICU length of stay with implementation of nurse-driven protocolized sedation [ 43 ]. Whether the use of nurse-driven sedation protocols should be implemented or not, could be debated, but the abovementioned evidence show more advantages than drawbacks with such an approach.…”
Section: Discussionmentioning
confidence: 99%
“…19 A similar approach was trialed in a paediatric cardiac ICU and was associated with decreased opioid and benzodiazepine use without concomitant increase in other sedative drugs. 20 A trial in two neonatal ICUs found that the use of an analgesia and sedation protocol, including a standardised scoring tool, significantly increased staff satisfaction for both physicians and nurses (defined as staff feeling that pain and sedation management was "good or very good"). 4 Implementation of the protocol was associated with higher cumulative exposure to opioids, although with the majority of scoring assessments (65%) indicating that analgesia and sedation were at goal.…”
Section: Discussionmentioning
confidence: 99%
“…37 Nurse-driven sedation protocols may standardize the use of sedation and analgesic medications. 48,49 Little research has examined the use of nonpharmacologic comfort measures and their effectiveness in reducing pain among infants after cardiac surgery; however, recent studies of massage and skin-to-skin care have demonstrated feasibility and initial evidence of pain reduction. 43,50 More research is needed to provide evidence that can inform the integration of nonpharmacologic comfort measures into nursing practice.…”
Section: Discussionmentioning
confidence: 99%